COMPARISON OF PHYSICOCHEMICAL CHARACTERISTICS AND COMPOSITION OF BERGAMOT OIL SEED EXTRACTED FROM THREE DIFFERENT CULTIVARS - Sicari, Vincenzo; PELLICANO, TERESA MARIA; Messina, Francesco (Emirates Journal of Food and Agriculture, 2017)
The effect of cultivar on bergamot seed oil composition from three cultivars (Castagnaro, Femminello and Fantastico) grown in province of Reggio Calabria (Southern Italy) was investigated. The maximum oil yield was 35.01 g 100 g-1 in Castagnaro cultivar. The acidity values of the oil varied between 0.62 and 0.87 mg NaOH per g of oil, and peroxide values varied between 11.67 meq/kg and 14.30 meq/kg. The major fatty acid of the extracted seed oils was oleic (31% to 34%), followed by linoleic (27% to 30%) and palmitic (21% to 23%). There were also other acids found small quantities such as stearic, arachidic and linolenic. β-sitosterol was the predominant sterol that accounted for more than 70% of total sterols. Other sterols, campesterol, stigmasterol, ∆5-avenasterol, cholesterol and 2,4-metylencolesterol were detected in most of the oils. The results of the study showed that the bergamot seeds under study and the extracted oil have the potential of being used as the source of edible oil.